The Microbiological Drivers of Temporally Dynamic Dimethylsulfoniopropionate Cycling Processes in Australian Coastal Shelf Waters - O’Brien, James; McParland, Erin L.; Bramucci, Anna R.; Ostrowski, Martin; Siboni, Nachshon; Ingleton, Timothy; Brown, Mark V.; Levine, Naomi M.; Laverock, Bonnie; Petrou, Katherina; Seymour, Justin (Frontiers in Microbiology, 2022)
The organic sulfur compounds dimethylsulfoniopropionate (DMSP) and dimethyl sulfoxide (DMSO) play major roles in the marine microbial food web and have substantial climatic importance as sources and sinks of dimethyl sulfide (DMS). Seasonal shifts in the abundance and diversity of the phytoplankton and bacteria that cycle DMSP are likely to impact marine DMS (O) (P) concentrations, but the dynamic nature of these microbial interactions is still poorly resolved. Here, we examined the relationships between microbial community dynamics with DMS (O) (P) concentrations during a 2-year oceanographic time series conducted on the east Australian coast. Heterogenous temporal patterns were apparent in chlorophyll a (chl a) and DMSP concentrations, but the relationship between these parameters varied over time, suggesting the phytoplankton and bacterial community composition were affecting the net DMSP concentrations through differential DMSP production and degradation. Significant increases in DMSP were regularly measured in spring blooms dominated by predicted high DMSP-producing lineages of phytoplankton (Heterocapsa, Prorocentrum, Alexandrium, and Micromonas), while spring blooms that were dominated by predicted low DMSP-producing phytoplankton (Thalassiosira) demonstrated negligible increases in DMSP concentrations. During elevated DMSP concentrations, a significant increase in the relative abundance of the key copiotrophic bacterial lineage Rhodobacterales was accompanied by a three-fold increase in the gene, encoding the first step of DMSP demethylation (dmdA). Significant temporal shifts in DMS concentrations were measured and were significantly correlated with both fractions (0.2–2 μm and >2 μm) of microbial DMSP lyase activity. Seasonal increases of the bacterial DMSP biosynthesis gene (dsyB) and the bacterial DMS oxidation gene (tmm) occurred during the spring-summer and coincided with peaks in DMSP and DMSO concentration, respectively. These findings, along with significant positive relationships between dsyB gene abundance and DMSP, and tmm gene abundance with DMSO, reinforce the significant role planktonic bacteria play in producing DMSP and DMSO in ocean surface waters. Our results highlight the highly dynamic nature and myriad of microbial interactions that govern sulfur cycling in coastal shelf waters and further underpin the importance of microbial ecology in mediating important marine biogeochemical processes.